Creation ethics genetics, reproduction, and quality of life - DeGrazia, David (New York ; Oxford : Oxford University Press, 2012)
'Creation Ethics' illuminates an array of issues in 'reprogenetics' through the lens of moral philosophy. With novel frameworks for understanding prenatal moral status and human identity, David DeGrazia tackles the ethics of abortion and embryo research, genetic enhancement and prenatal genetic interventions, and much more.
Description based on online resource; title from PDF title page (viewed on July 9, 2012).
Includes bibliographical references and index.
Keywords: Human reproductive technology -- Moral and ethical aspects; Medical genetics -- Moral and ethical aspects